2002
DOI: 10.1016/s0002-9440(10)64882-1
|View full text |Cite
|
Sign up to set email alerts
|

β1 and β2 Integrins Mediate Adhesion during Macrophage Fusion and Multinucleated Foreign Body Giant Cell Formation

Abstract: An in vitro system of interleukin (IL)-4-induced human monocyte-derived macrophage fusion was used to investigate the cell/substrate adhesive mechanisms that support multinucleated foreign body giant cell (FBGC) formation. Monocytes were cultured for 3 days and IL-4 was added to induce macrophage fusion and FBGC formation by day 7. Functionally defined anti-integrin antibodies demonstrated that initial monocyte adhesion is mediated by beta2 integrins, whereas during the induction of macrophage fusion by IL-4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
183
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 204 publications
(199 citation statements)
references
References 54 publications
11
183
1
Order By: Relevance
“…In this regard, McNally and Anderson 14 have demonstrated that anti-b2 antibodies inhibited not only adhesion but also the MGC formation, suggesting that the fusion step is also mediated by b2 integrins. However, whether Mac-1 was involved in this step has not been determined in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, McNally and Anderson 14 have demonstrated that anti-b2 antibodies inhibited not only adhesion but also the MGC formation, suggesting that the fusion step is also mediated by b2 integrins. However, whether Mac-1 was involved in this step has not been determined in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…23 The role of b2 integrins in macrophage fusion remains controversial. Although previous studies with function-blocking antibodies implicated b2 integrins in macrophage fusion, 14 other reports concluded that b2 integrins play a minor role. 24 Thus, definitive experimental evidence for the role of b2 integrins and, in particular, of Mac-1 is lacking, and the involvement of a D b 2 in fusion is unclear.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…In vitro, we have demonstrated that the lymphokines IL-4 (McNally 1995) or IL-13 (DeFife 1997) induce macrophage fusion and the formation of FBGC that are morphologically indistinguishable from the IL-4-induced FBGC that form on implanted materials in vivo (Zhao 1991, Kao 1995. IL-4-induced macrophage fusion is dependent on the activity of a classic endocytic/phagocytic receptor, the mannose receptor (McNally 1996), and exhibits multiple other features of a phagocytic process (McNally 2005) that is supported by cell/substrate adhesive interactions between select β1 and β2 integrins and vitronectin (McNally 2002, McNally 2007a, McNally 2007b. Interestingly, we found that α-tocopherol is also a potent macrophage fusion factor, and that diacylglycerol kinase activity is required for both α-tocopherol-and IL-4-induced FBGC formation .…”
Section: Introductionmentioning
confidence: 99%
“…RGD was used as a positive control surface for macrophage development and adhesion and FBGC formation, as previously reported. [37][38][39] Adsorbed RGD is widely recognized for its adhesion-promoting capabilities in that it presents multiple copies of the RGD (arginine-glycine-aspartate) cell attachment sequence to integrin receptors, thus facilitating their engagement.…”
Section: Adsorption Of Human Fg and Rgd Peptidementioning
confidence: 99%